Polymethoxyflavones from Nicotiana plumbaginifolia (Solanaceae) Exert Antinociceptive and Neuropharmacological Effects in Mice - Shajib, Md. Shafiullah; Rashid, Ridwan B.; Ming, Long C.; Islam, Shanta; Sarker, Md. Moklesur R.; Nahar, Lutfun; Sarker, Satyajit D.; Datta, Bidyut K.; Rashid, Mohammad A. (Frontiers in Pharmacology, 2018)
Polymethoxylavones (PMFs) are known to exhibit significant anti-inflammatory and neuroprotective properties. Nicotiana plumbaginifolia, an annual Bangladeshi herb, is rich in polymethoxyflavones that possess significant analgesic and anxiolytic activities. The present study aimed to determine the antinociceptive and neuropharmacological activities of polyoxygenated flavonoids namely- 3,3′,5,6,7,8-hexamethoxy-4′,5′-methylenedioxyflavone (1), 3,3′,4′,5′,5,6,7,8-octamethoxyflavone (exoticin) (2), 6,7,4′,5′-dimethylenedioxy-3,5,3′-trimethoxyflavone (3), and 3,3′,4′,5,5′,8-hexamethoxy-6,7-methylenedioxyflavone (4), isolated and identified from N. plumbaginifolia. Antinociceptive activity was assessed using the acetic-acid induced writhing, hot plate, tail immersion, formalin and carrageenan-induced paw edema tests, whereas neuropharmacological effects were evaluated in the hole cross, open field and elevated plus maze test. Oral treatment of compounds 1, 3, and 4 (12.5–25 mg/kg b.w.) exhibited dose-dependent and significant (p < 0.01) antinociceptive activity in the acetic-acid, formalin, carrageenan, and thermal (hot plate)-induced pain models. The association of ATP-sensitive K+ channel and opioid systems in their antinociceptive effect was obvious from the antagonist effect of glibenclamide and naloxone, respectively. These findings suggested central and peripheral antinociceptive activities of the compounds. Compound 1, 3, and 4 (12.5 mg/kg b.w.) demonstrated significant (p < 0.05) anxiolytic-like activity in the elevated plus-maze test, while the involvement of GABAA receptor in the action of compound 3 and 4 was evident from the reversal effects of flumazenil. In addition, compounds 1 and 4 (12.5–25 mg/kg b.w) exhibited anxiolytic activity without altering the locomotor responses. The present study suggested that the polymethoxyflavones (1–4) from N. Plumbaginifolia could be considered as suitable candidates for the development of analgesic and anxiolytic agents.